2021
DOI: 10.3389/fnagi.2021.724990
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Plasma Total Homocysteine With Dementia With Lewy Bodies: A Case-Control Study

Abstract: Background: Elevated plasma total homocysteine (tHcy) level, a known risk factor for vascular disease, is reported to be an independent risk factor for cognitive impairment and Alzheimer’s disease (AD) in most studies. tHcy may also be associated with dementia with Lewy bodies (DLB).Objective: To investigate the association between plasma tHcy levels and DLB or AD.Methods: This is a case-control study including 132 DLB patients, 264 AD patients, and 295 age-matched healthy controls. We used multivariate logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…We generated Kaplan-Meier survival curves using the median survival time from disease onset and the first visit were 81 (95% CI 69.09-92.91) and 45 (95% CI 34.78-55. 22) months, respectively. The median survival time from the first visit to death in mild dementia and moderate to severe dementia was comparable at 59 (95% CI 34.32-83.68) and 41 (95% CI 30.15-51.85) months, respectively (log-rank χ 2 = 7.76, p < 0.005) (Figure 2).…”
Section: Survival Time From First Visit and Disease Onset By Groupsmentioning
confidence: 93%
See 2 more Smart Citations
“…We generated Kaplan-Meier survival curves using the median survival time from disease onset and the first visit were 81 (95% CI 69.09-92.91) and 45 (95% CI 34.78-55. 22) months, respectively. The median survival time from the first visit to death in mild dementia and moderate to severe dementia was comparable at 59 (95% CI 34.32-83.68) and 41 (95% CI 30.15-51.85) months, respectively (log-rank χ 2 = 7.76, p < 0.005) (Figure 2).…”
Section: Survival Time From First Visit and Disease Onset By Groupsmentioning
confidence: 93%
“…Visual hallucinations, specifically formed and detailed visual hallucinations and illusions, that were complained about by the patient and/or caregiver were determined by confirmation and quantification according to the hallucinations item of the Neuropsychiatric Inventory scores (NPI) 20,21 . Parkinsonism was rated as present when the neurological exam showed extrapyramidal signs (tremor, bradykinesia, and/or rigidity) 22 . RBD was confirmed by caregivers who noted five or more behaviors that are mentioned in the RBD screening questionnaire (RBD‐SQ) or by someone who was diagnosed using overnight video polysomnography 23,24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [ 115 ] recently performed a retrospective case–control study including 132 dementia with Lewy body (LBD) patients, 264 AD patients, and 295 age-matched healthy controls. They found that elevated plasma tHCy levels were associated with LBD, and more strongly so than with AD.…”
Section: Homocysteine and Degenerative Brain Diseasesmentioning
confidence: 99%
“…Work published later than 2000, which we review below, kept neglecting the issue. Most of the studies exploring the role of HCy levels on the dementias do not report data from multi-domain neuropsychological examination [ 85 , 86 , 88 , 89 , 92 , 93 , 95 , 98 , 99 , 102 , 103 , 104 , 105 , 109 , 112 , 115 , 116 , 117 , 118 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Typically, authors focus on the general cognitive status of the patient, and thus report data from neuropsychological screening tools, such as the Mini Mental State Examination (MMSE).…”
Section: Homocysteine and Cognitive Functionsmentioning
confidence: 99%